Technological breakthroughs and productivity growth - Harald Edquist; Magnus Henrekson (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
This study consists of an examination of productivity growth following three major technological breakthroughs: the steam power revolution, electrification and the ICT revolution. The distinction between sectors producing and sectors using the new technology is emphasized. A major finding for all breakthroughs is that there is a long lag from the time of the original invention until a substantial increase in the rate of productivity growth can be observed. There is also strong evidence of rapid price decreases for steam engines, electricity, electric motors and ICT products. However, there is no persuasive direct evidence that the steam engine producing industry and electric machinery had particularly high productivity growth rates. For the ICT revolution the highest productivity growth rates are found in the ICT-producing industries. We suggest that one explanation could be that hedonic price indexes are not used for the steam engine and the electric motor. Still, it is likely that the rate of technological development has been much more rapid during the ICT revolution compared to any of the previous breakthroughs.
Keywords: N10; O10; O14; O40; 330; electrification; general purpose technologies; ICT revolution; productivity growth; steam power; Technological breakthroughs; Produktivität; Technischer Fortschritt